Pembuatan Website untuk Komunitas PPKM - Kenny Andre Sahertian; Djoni Haryadi Setiabudi; Leo Willyanto Santoso (Jurnal Infra, 2017)
Mollucan Christian Youth Fellowship has many members who don’t just stay in Surabaya, but there is also some are living and working in several cities in Indonesia like Ambon, Masohi, Sorong, Jayapura, Jakarta and several cities in Java and Kalimantan. Because many members are scattered throughout Indonesia, this causes difficulities in communating. The purpose of this thesis is making a website as a media of news, information and communication among members of fellowship.In developing this website of Community of Mollucan Christian Youth Fellowship, several technologies are used such as; notepad++, XAMPP and browser, HTML, CSS3, PHP, and MySQL to create a database. The author also uses Instagram API to integrate photos on social media Instagram to the website.This research has been successfully created a website which is used as a media of news, information and communication around the community and has been successfully through testing all of the features that existed on this website.